Pemanfaatan limbah botol kaca dalam meningkatkan pendapatan keluarga di Kabupaten Takalar - Romansyah Sahabuddin; Abdi Akbar Arief; Muhammad Djufri (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This event is aimed to empower the community through training making handicrafts with use waste glass bottles oriented creativity so that it can produce new product contributing to create new jobs and improve family income the community. In addition it is also a big step to act would make people aware that it is important to take care of this environment live in a way reduce plastic bottle full of liquid waste through the ability the creativity of the community in the village Lengkese Subistrict Mangarabombang District Takalar. A glass bottle in the community in general and especially in some rural usually used as a storage place for drinking water and often stacked intermediary is then sold back to second-hand goods relatively cheap. But thus through values creativity, a glass bottle can be processed into something useful aesthetic is in and of itself has a promising into the price. Product that can be produced from a bottle former through hands skilled can be sold in market and having competitiveness not inferior to other kind of as exhibits lights, glass, and ashtray. Also the charges manufacturing expensive and easily make it, and having selling price that high.